Variability of Executive Function Performance in Preschoolers with Developmental Language Disorder - Kapa, Leah L.; Erikson, Jessie A. (Seminars in Speech and Language, 2019)
Although results vary across individual studies, a large body of evidence suggests that children with developmental language disorder (DLD) have domain-general deficits in executive function compared with peers with typically developing language. Poorer performance for children with DLD has been reported on verbal and nonverbal measures of sustained selective attention, working memory, inhibition, and shifting. However, examination of the variability of task scores among both children with and without DLD reveals a wide range of executive function performance for both groups. Additionally, using executive function scores to classify children into DLD versus typical groups results in classification accuracy that is not clinically useful. This evidence indicates that group-level differences in executive function abilities between children with and without DLD cannot be applied at the individual level. Many children with DLD appear to have intact executive function abilities, which undermines the possibility that poor executive functioning causes language deficits in this population. However, a substantial number of children with DLD also have executive function deficits, and, therefore, therapy approaches with this population should consider both their language and executive function abilities.
Keywords: developmental language disorder; specific language impairment; executive function; attention